DEVELOPMENT OF EDUTAINMENT-BASED MECHANICAL ENGINEERING DRAWING LEARNING MEDIA USING THE CANVA APPLICATION - Pamungkas, Tabah Putra; Prihantoro, Constantinus Rudy; Sukarno, Ragil (Department of Mechanical Engineering Education, 2025)
Education and learning are developing in accordance with the development of science and technology. The education quality could be improved by changing a conventional learning media into learning media that can increase student motivation so that students can more easily understand the learning material. This research aims to develop and design edutainment-based learning media using the Canva application in the subject of Mechanical Engineering Drawing. The research was carried out using the Research and Development (R&D) method with a 4D development model, which must go through a validation process from experts as a successful process of the feasibility test of the product developed before it is later used by students. This research offers a novelty by integrating specific edutainment elements in the Canva application for Machine Engineering Drawing learning, which has not been explored much in this context before. This innovation creates a more interactive and engaging learning experience, expected to significantly improve material comprehension and retention compared to conventional methods. The results of the feasibility test of edutainment-based mechanical engineering drawing learning media using the Canva application obtained a percentage of 96% from material expert validators, 88% from media expert validators, and 86% from the results of the learning media feasibility test conducted by students. From the results of the test, it can be concluded that Edutainment-Based Mechanical Engineering Drawing Learning Media Using the Canva Application